At the Borders of the 19th-Century Bourgeois Morality: Female Adultery as a Constitutive Exterior of Marriage - Nastasescu, Diana (Tropelías: Review of Literary Theory and Comparative Literature, 2024)
The theme of this study falls within the axiological revision, from a feminist perspective, of the readings and reading methods that have shaped us as readers and as social subjects. Under these ideas, three aspects will be addressed: on one hand, the signing of the sexual contract by women; on the other, adultery as a catalyst for the shift from the private sphere to the public sphere; and finally, the transition from central to peripheral subjects experienced by unfaithful women. All this within the broader framework that assumes the need for adulterous transgression to establish the boundaries of marriage, on the periphery of which the adulteresses remain once their adulteries are discovered. To do this a corpus made up of the following novels will be explored: Madame Bovary (1856) by Gustave Flaubert, O Primo Basílio (1878) by Eça de Queirós, La Regenta (1884-1885) by Leopoldo Alas, Blanca Sol (novela social) (1888) by Mercedes Cabello de Carbonera and Effi Briest (1895) by Theodor Fontane.
Keywords: comparative literature; adultery; bourgeois morality; oustide constitutive; domesticity